Genome‑wide analysis of the MYB gene family in pumpkin - Xu, Minyan; Fu, Jingjing; Ni, Ying; Zhang, Chenchen (PeerJ, 2024)
The MYB gene family exerts significant influence over various biological processes and stress responses in plants. Despite this, a comprehensive analysis of this gene family in pumpkin remains absent. In this study, the MYB genes of Cucurbita moschata were identified and clustered into 33 groups (C1-33), with members of each group being highly conserved in terms of their motif composition. Furthermore, the distribution of 175 CmoMYB genes across all 20 chromosomes was found to be non-uniform. Examination of the promoter regions of these genes revealed the presence of cis-acting elements associated with phytohormone responses and abiotic/biotic stress. Utilizing quantitative real-time polymerase chain reaction (qRT-PCR), the expression patterns of 13 selected CmoMYB genes were validated, particularly in response to exogenous phytohormone exposure and various abiotic stressors, including ABA, SA, MeJA, and drought treatments. Expression analysis in different tissues showed that CmoMYB genes are expressed at different levels in different tissues, suggesting that they are functionally divergent in regulating growth and abiotic stresses. These results provide a basis for future studies to characterize the function of the MYB gene family under abiotic stresses in pumpkins.
Keywords: MYB; Gene; Cis-acting elements; ABA; SA; MeJA; Abiotic/biotic stresses; Transcription factors; Genome-wide analysis; Pumpkin